К морфо-функциональному анализу шеи вороны серой (Corvus cornix L.) - Попова, М.Ф. (Вестник зоологии, 1972)
In order to investigate the biomechanical peculiarities of the bird's neck, the crow's neck was studies as а model. The method of biomechanical analysis was used for the first time. То understand the biomechanical peculiarities of the crow's neck during the fly and getting food, the author described the skeleton, ligaments апс1 muscles. Some muscles аrе described for the first time. А comparison made of the crow's neck with that of 62 species from 15 orders shows а similar structure in Galliformes, Procellariiformes, Cruiformes, Falconiformes, Columbi formes, Anseriformes. The loons and grebes differ in conection with the aquatic 1ife. Ciconiiformes and Steganopodes show а transition from the common constructions of the storks, ibises, Scopus umbretta, Fregata to «darting stroke» of the Sula, herons, Pelecanus and Plotus.